2018
DOI: 10.2147/ijwh.s151784
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for maternal mortality in referral hospitals in Nigeria: a multicenter study

Abstract: IntroductionWhile reports from individual hospitals have helped to provide insights into the causes of maternal mortality in low-income countries, they are often limited for policymaking at national and subnational levels. This multisite study was designed to determine maternal mortality ratios (MMRs) and identify the risk factors for maternal deaths in referral health facilities in Nigeria.MethodsA pretested study protocol was used over a 6-month period (January 1–June 30, 2014) to obtain clinical data on pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
49
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 16 publications
12
49
2
1
Order By: Relevance
“…This may be attributed to the socio-cultural beliefs of participants, as pregnant women in Abeokuta would rather consult religious leaders or traditional healers for information about their health. This agrees with the indings of Na iu, Kabir & Adiukwu, 2016; Ntoimo et al [10,11]. Respondents also agreed that grief and depression could lead to maternal mortality.…”
Section: Causes Of Maternal Mortalitysupporting
confidence: 87%
See 1 more Smart Citation
“…This may be attributed to the socio-cultural beliefs of participants, as pregnant women in Abeokuta would rather consult religious leaders or traditional healers for information about their health. This agrees with the indings of Na iu, Kabir & Adiukwu, 2016; Ntoimo et al [10,11]. Respondents also agreed that grief and depression could lead to maternal mortality.…”
Section: Causes Of Maternal Mortalitysupporting
confidence: 87%
“…Risk of maternal mortality is increased in women who have had two children and above [9]. The higher the number of antenatal visits, the lower the likelihood of maternal mortality [10,11]. Azuh, Azuh, Iweala, Adeloye, Akanbi & Mordi [12] reported that place of delivery of last birth is signi icant to maternal mortality.…”
Section: Introductionmentioning
confidence: 99%
“…The antenatal period provides ample opportunity for health workers to educate women, offer screening, diagnosis and treatment services for pregnancy-related conditions, and refer women for specialized interventions. It is therefore imperative that pregnant women take full advantage of antenatal care services [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Available evidence reveal that Nigeria has not attained the expected success in antenatal coverage and reduction in maternal mortality ratio [5,6]. The poor maternal health outcome in Nigeria could be a result of poor ANC coverage and utilization [7,8].…”
Section: Antenatal Care Utilizationmentioning
confidence: 99%
“…The poor maternal health outcome in Nigeria could be a result of poor ANC coverage and utilization [7,8]. The importance of ANC services in enhancing maternal health during pregnancy and influencing the outcomes of pregnancy have been shown in previous studies [6,[9][10][11]. ANC allows for prevention, early identification and management of conditions that could be aggravated by pregnancy or threatening to the mother and/or her baby.…”
Section: Antenatal Care Utilizationmentioning
confidence: 99%